Decomposing the Changes of the Divisia Price Index: Application to Inflation in the Philippines - FUJII, Tomoki (Institutional Knowledge at Singapore Management University, 2011)
We propose a method to decompose the logarithmic change of the Divisia price index into the pure price effect, the preference effect and the substitution effect. Our empirical results in the Philippines shows the effects of preference change on the Divisia price index are heterogeneous but positive across all regions and income deciles. However, they are dominated by the pure price effect.